(untitled) (Journal of Engineering, 2008)
In this research, a procedure to solve problems of unsteady flow to wells in confined aquifers by the computer is developed. The solution is based on the [THEIS:1935] procedure to solve such problems. The developed procedure is applied to (14) different sets of well – test data, including a predicted ideal one. The respective problems are solved completely by the computer without the need to construct or to refer to tables or nomographs; this, accordingly, deletes the role of personal judgment and the need to a high skill. The applications indicate that the developed solution procedure is simple, easy to use, elaborate, superiorly fast in giving the required results, and comparatively accurate. Despite that the developed solution procedure has been set for the case of a pumped well in an ideal confined aquifer, it is basically general; the computer program can be easily modified to fit the solution of problems of the other cases of groundwater flow to wells after introducing the additions that consider the respective boundary conditions